2017
DOI: 10.3390/su9112152
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Evacuation Warnings Prior to a Hurricane Disaster

Abstract: Abstract:The key purpose of this paper is to demonstrate that optimization of evacuation warnings by time period and impacted zone is crucial for efficient evacuation of an area impacted by a hurricane. We assume that people behave in a manner consistent with the warnings they receive. By optimizing the issuance of hurricane evacuation warnings, one can control the number of evacuees at different time intervals to avoid congestion in the process of evacuation. The warning optimization model is applied to a cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…It can be seen how trucks is the most widely used type of vehicle, even though helicopters, ambulances and rafts are also used at certain points. ( [15,17,19], [24,24,24]) ( [8,14,18,20,22], [3,36,36,36,3] In order to further evaluate the performance of the model in different situations, several specific modifications were performed on the case study and the resulting lexicographical goal programming problems were resolved again. For example, as stated by the International Civil Aviation Organization of OCHA [58], the Palu airport suffered a great amount of damage and it could not be used during the first hours of the evacuation operation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen how trucks is the most widely used type of vehicle, even though helicopters, ambulances and rafts are also used at certain points. ( [15,17,19], [24,24,24]) ( [8,14,18,20,22], [3,36,36,36,3] In order to further evaluate the performance of the model in different situations, several specific modifications were performed on the case study and the resulting lexicographical goal programming problems were resolved again. For example, as stated by the International Civil Aviation Organization of OCHA [58], the Palu airport suffered a great amount of damage and it could not be used during the first hours of the evacuation operation.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, supported evacuation is needed if individuals require greater and specific support (for example, an ambulance) to be transported from the unsafe areas to safer ones. Self-evacuation and assisted evacuation (both often referred as car-based evacuation) have been vastly studied in the literature, facing problems like traffic congestion, clogging, bottlenecks, density waves, oscillations, patterns and panic, usually solved by nonlinear techniques and queuing theory [18,[21][22][23][24][25]. However, and according to Houston et al [26], sometimes self evacuation is not an option.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…These findings indicated that the Government's information release mechanism before the arrival of a typhoon can play an important role in the evacuation process. Previous studies have shown that sending warnings judiciously (scientific information release mechanism) could help evacuation efficiency and reduce the cost of congestion in evacuation [45,46]. Thus, effective communication to people in hazardous areas in the process of evacuation can guide and promote the evacuation strategy of the evacuated groups.…”
Section: Impact On Cost Reduction In Evacuation Process Due To Governmentioning
confidence: 99%
“…A study of 12 hurricanes occurring between 1961 and 1989 ( 10 ) determined that the significant factors related to the evacuate–stay decision were advisory or mandatory evacuation orders and how individuals perceive the emergency management officials (source of information, content, and accuracy of evacuation message). Despite the substantial evacuation notice in coastal areas, some people do not evacuate because of hurricane impact uncertainty or personal concerns ( 18 ). Areas further inland can also be at high risk for some hurricane hazards such as wind and rainfall flooding that may motivate people to evacuate even though they do not receive mandatory evacuation notices ( 9 , 19 , 20 ).…”
Section: Related Workmentioning
confidence: 99%
“…Although local and national media are the most common for official notice transmission, they are not personalized enough ( 22 ). Social networks such as peers and relatives with whom one shares hazard-specific risks will affect personal judgment ( 3 , 18 , 23 ). Later, Sadri et al, ( 24 ) found that those with recovery assistance from neighbors, stronger personal networks, and higher levels of social capital experienced faster recovery.…”
Section: Related Workmentioning
confidence: 99%